(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
This article investigates communicative taboo interrelation with other cultural bans. It defines their specific features and identifies communicative taboo peculiar signs on the Ukrainians’ speech basis.